U.S. GEOSTRATEGIC AND ECONOMIC INTERESTS AND ISRAELI-PALESTINIAN CONFLICT - Egwu, Urom, Charles; Michelle, Okigwe, Chioma; Ogbonna, Okpara, Emmanuel (PT. Antis International Publisher, 2025)
Objective: This study explores the U.S. geostrategic and economic interests in the Israeli-Palestinian conflict, analyzing how these interests shape U.S. policy and contribute to the ongoing deadlock in peace negotiations. Method: The research adopts a qualitative approach, utilizing secondary sources such as textbooks, journal articles, newspapers, government publications, and international news outlets, which were analyzed using content analysis. Results: The findings reveal that U.S. policy is predominantly driven by geostrategic goals, such as maintaining regional dominance, securing Israel's security, and accessing critical resources like oil. U.S. support for Israel has reinforced power imbalances, undermining the possibility of a fair peace process for Palestine. Despite numerous peace initiatives, U.S. strategic interests have consistently overshadowed efforts toward equitable solutions. Novelty: By applying Realism as a theoretical framework, this study provides insights into the dominance of power and security concerns in shaping U.S. policy in the Israeli-Palestinian conflict, calling for a reassessment of U.S. economic and security policies to prioritize Palestinian sovereignty and fair development. The study recommends multilateral diplomacy to ensure equitable representation in peace negotiations.